Pioneer and Mentoring Disaster Preparedness Schools (SSB) at Statte Junior High School 13, Ternate City, North Maluku Province - Hamid, Fatma; Achmad, Rahim; Saprudin, Saprudin; Rahman, Nurdin A; Rahman, Mardia Hi.; Muhammad, Nurlaela; Sahjat, Sumarni (Mattawang: Jurnal Pengabdian Masyarakat, 2025)
Indonesia, located at the confluence of three major tectonic plates, this situation allows Indonesia to always be under threat of geological disasters. Ternate Island with Mount Gamalama, located in the western part of Halmahera Island, is also a threat of geological disasters. SMP Negeri 13 Kota Ternate, located in a high-risk area of earthquake and volcanic eruption, became the location of the Disaster Preparedness School (SSB) implementation. This activity aims to implement the concept of Disaster Preparedness School to reduce disaster risks and impacts through a comprehensive approach. The research method used a participatory approach with activities including disaster socialization, rescue simulations, science projects to make simple earthquake detection devices, installation of disaster signs, and lectures from the Regional Disaster Management Agency (BPBD). SSB implementation was carried out through three stages: organizing, interpreting, and applying. The results of the activities show a high level of school resilience with six supporting aspects, but there are still obstacles such as student turnover and limited funds. SSB activities contribute significantly in increasing the awareness and preparedness of school community in facing disasters. It can be concluded that the implementation of SSB in SMP Negeri 13 Ternate City successfully integrated disaster mitigation in the curriculum and school activities. The main recommendation is to increase socialization, implement routine simulations, and develop the resilience aspects of the school in a comprehensive manner.